Frame Pemberitaan Terkait Reuni Persaudaraan Alumni (PA) 212 Pada Tahun 2018 Di Media Republika Online - Simorangkir, Sendi Romadhon; Kamalludin, Kamalludin; Yono, Yono (KOMUNIKA, 2019)
This study aims to determine and examine the reporting frame regarding the reunion of the 212 Alumni Brotherhood. Research methods is qualitative content analysis with Robert N. Entman. Research results from online Republika constructs news related to the reunion of the alumni fraternity 212 through the perspective of Islamic ideology. This shows that Republika Online illustrates a positive thing about the implementation and impact of the implementation of the alumni reunion fraternity 212. It is known that there are also imbalances in the news regarding the reunion 212. Based on Robert N. Entman's framing which has four namely Define Problem, Diagnose Causes, Make Moral Judgement, Treatment Recommendation. It can be concluded that Republika Online news analysis seems to support the implementation of the alumni brotherhood reunion in accordance with the perspective of media ideology, namely Islamic ideology. The suggestion is Republika Online editor in order to maintain the balance of the news by paying attention to the cover both side on each issue, because there is some news that are not cover both sides. So, readers can find out the full contents of the news on one news issue.AbstrakPenelitian ini bertujuan untuk mengetahui dan menganalisa framing berita tentang reuni Persaudaraan Alumni 212. Penelitian ini menggunakan metode analisis kualitatif dari Robert N. Entman. Penelitian bersumber mengenai kontruksi berita Republika Online terkait dengan reuni Persaudaraan Alumni 212 dengan perspektif ideologi Islam. Hal ini menunjukkan bahwa Republika Online menggambarkan hal yang positif tentang implementasi dan efek dari reuni Persaudaraan Alumni 212. Banyak sumber lain yang memberikan berita yang tidak seimbang tentang reuni 212. Robert N. Entman dengan teori Analisis Framing Modelnya yaitu dibagi menjadi Define Problem, Diagnose Causes, Make Moral Judgement, dan Treatment Recommendation. Dapat disimpulkan bahwa berita Republika Online mendukung implementasi dari reuni Persaudaraan Alumni 212 sesuai dengan perspektif ideologi media, yaitu ideologi Islam. Sarannya adalah editor Republika Online untuk menjaga keseimbangan berita dengan memperhatikan kedua belah sisi pada setiap masalah, karena ada beberapa berita yang tidak mencakup kedua sisi. Jadi, pembaca dapat mengetahui isi penuh berita pada suatu masalah.